Relay-Based Positioning in TDMA Networks - Lee, Kyuman; Baek, Hoki; Lim, Jaesung (IEEE Systems Journal, 2018)
In this letter, we propose relay-based positioning in time division multiple access (TDMA) networks, called RPT. Although the concept of relay-based positioning is an improvement over the performance of relative navigation (RelNav), there are two problems to be solved when applying the relay concept to a TDMA network. First, measurement errors caused by mobility may degrade user accuracy because positioning references transmit navigation messages at their assigned times in TDMA, unlike conventional navigation systems, where all references continuously transmit. Second, a selection algorithm among airborne nodes is needed to relay messages to users. An RPT frame is designed to assign the slots for the broadcast and relay of navigation messages consecutively to minimize the effect of mobility. The selection algorithm determines the optimum set of airborne relays by selecting evenly distributed nodes depending on their distances to the master station. The simulation results indicate that RPT significantly improves user accuracy over RelNav.
Keywords: Algorithm design and analysis; Distributed nodes; Navigation messages; Relative navigation; Relays; Resource management; Selection algorithm; Time division multiple accesses (TDMA); Hybrid systems; Kalman filters; radio navigation; relays; time division multiple access